Intrathecal dose intensification by CNS status at diagnosis in the treatment of children with acute lymphoblastic leukemia. Issue 1 (1st January 2019) - Jastaniah, Wasil; Elimam, Naglla; Abdalla, Khalid; AlAzmi, Aeshah A.; Algamal, Amal; Felimban, Sami
ABSTRACT: Objectives: Acute lymphoblastic leukemia (ALL) with CNS2 status predicts inferior outcome and a high rate of CNS relapse, similar to overt CNS leukemia (CNS3). The purpose of this study was to determine if intrathecal (IT) dose intensification during induction would improve outcomes and reduce CNS relapse for CNS2 disease. Methods: From January 2001 to December 2014, children (1–14 years) with newly diagnosed ALL were treated at the Princess Noorah Oncology Centre (PNOC) following modifications of the Children's Oncology Group (COG) protocols. We intensified IT methotrexate (ITM) during induction for patients with CNS2 disease. Patients were evaluated for overall survival (OS), disease-free survival (DFS), and cumulative incidence of relapse (CIR). Results: 449 children with T-cell (14.3%) or B-cell (85.7%) ALL were treated using PNOC-SR or PNOC-HR regimens (Jan 2001- Dec 2007) or CALL08 regimens (Arm A [SR], Arm B [IR], and Arm C [HR]) (Jan 2008 - Dec 2014). The 5-year OS, DFS, and CIR were 87.2 ± 1.6%, 81.7 ± 1.9%, and 13.0 ± 1.7%, respectively. The OS and DFS of patients with CNS2 were significantly superior to that of patients with CNS3 ( P   =  0.025 and P  = 0.019, respectively). Patients with CNS2 had similar OS and DFS to those with CNS1. None of the patients with CNS2 at initial diagnosis experienced CNS relapse. Conclusions: ITM intensification during induction was associated with elimination of CNS recurrence in patients with CNS2 disease and childhood ALL. Controlled studies are needed to confirm this observation.